A clinician-friendly test battery with a passing rate similar to a 'gold standard' return-to-sport test battery 1 year after ACL reconstruction: Results from a rehabilitation outcome registry. (January 2023) - Broman, Daniel; Piussi, Ramana; Thomeé, Roland; Hamrin Senorski, Eric
Abstract: Objectives: To 1) present passing rates for different clinician-friendly (CF) test batteries and 2) determine the relationship between passing CF test batteries and passing gold standard (GS) return-to-sport (RTS) muscle function testing, 1 year after ACL reconstruction. Study design: Cross-sectional registry study, level of evidence: 3. Setting: Primary care. Participants: Data from 588 patients (52% women, mean age 29.3 ± 9.8 years) were extracted from the Project ACL registry. Main outcome measures: The passing rates for the different test batteries. Results: The passing rate for GS test battery was 28% (95% CI, 24–32%) and the passing rate for the CF test battery with the lowest passing rate was 27% (95% CI 24–31%). The two CF test batteries with the strongest relationships with passing GS test battery showed that 51% (95% CI 43–59%) and 49% (95% CI 44–55%) of the patients who passed the respective CF test battery also passed the GS test battery. Conclusion: A CF test battery can be as demanding to pass as a GS test battery, 1 year after ACL reconstruction. However, passing a CF test battery only gives patients a chance similar to a "coin flip" of also passing a GS RTS test battery. Highlights: Most patients do not pass extensive test batteries, 1 year after surgery. A clinician-friendly test battery had similar passing rate as gold standard testing. The relationship between passing the different studied test batteries was poor. Psychological readiness was more demanding to recover than hop performance.